Regarding inspection report of fire pump at BRACU NCP - Bengal Technological Corporation Ltd.(BTCL) (Brac University, 2023)
This record consists of general correspondence regarding the regarding inspection report of fire pump at BRACU NCP of BRACU new campus project..